Kemampuan Mengelola Risiko pada UKM: Pengaruh Pengetahuan Akuntansi dan Lietrasi Keuangan - Melin Vaira Haswan; Halimatusyadiah Halimatusyadiah (AKUA: Jurnal Akuntansi dan Keuangan, 2025)
This study aims to examine the influence of accounting knowledge and financial literacy on the ability of SMEs to manage risk. This study used a quantitive approach and type of correlational researcg by describing primary data obtained directly from respondent, namely SMEs in Bengkulu Province. Purposive sampling was used with the following criteria: (1) the business has been active for a minimum of two years, and (2) it carries out financial recording and reporting. Data collection was done by distributing quetionnaires via google form. Partial Least Squares (PLS) is the methodology used in this study to evaluate the relationship between variables, with the help of the SmartPLS version 4.0 program. The results show accounting knowledge and financial literacy has a significant positive effect on risk management. The findings highlight the importance of strong accounting knowledge and financial literacy for SMEs, as these competencies help them identify, analyze, and mitigate financial risks that may disrupt business continuity. This aligns with the Knowledge-Based View (KBV), which emphasizes that the ability to manage and apply knowledge is essential for building stronger and more adaptive organizational capabilities.